A Unique Example Of Badash Folklore Creation - Nargiza Rahmatullaeva, (European Journal of Life Safety and Stability (2660-9630), 2022)
This article provides information about customs and historical traditions that exist in our country. The article focuses specifically on the music of "Badash". Reasonable opinions and comments within the scope of the topic are given. At the end of the article, conclusions and suggestions are given.